Strengthening climate resilience in mountainous areas - Kato, Takayoshi (OECD Publishing, 2021)
Mountainous areas are at the forefront of climate change. This working paper presents approaches to strengthening the resilience of human and natural systems in mountainous areas against the impacts of climate change. Chapter 1 provides an overview of climate-related hazards to ecosystems and communities in mountainous areas, especially in developing countries, and their exposure and vulnerability to those hazards. The chapter then examines various ways governments and development co‑operation providers can strengthen the climate resilience of mountain communities and ecosystems. Chapter 2 presents the case of the Indian state of Uttarakhand
Keywords: Development